Protein extraction from white, red, and black rice bran using modified three-phase partitioning: Evaluation of solubility, phytochemicals, and proteomics profiles - Miftahurrahmi, Miftahurrahmi; Estiasih, Teti; Sirinupong, Nualpun; Mahatmanto, Tunjung; Mubarok, Ahmad Zaki (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2025)
This study investigated the extraction, solubility profile, phytochemical content, and proteomic profile of rice bran protein (RBP) from white (WRB), red (RRB), and black rice bran (BRB) using a modified three-phase partitioning (TPP) method. Protein solubility peaked at: BRB pH 3.4 (5.40 mg/mL), WRB pH 3.5 (5.10 mg/mL), RRB pH 3.6 (5.03 mg/mL). These differences may be attributed to pigment-protein interactions and inherent protein composition. Phytochemical analysis at optimum solubility pH determined common and specific metabolites of RBP types. Bioactive compounds such as isoflavones, trehalose, and amino acids were found in all samples. At the same time, colored rice brans exhibited a wider profile of secondary metabolites such as phenolics, alkaloids, and steroidal glycosides. Proteomic profiling identified universal seed storage proteins, antioxidant enzymes, and stress proteins across all RBP types. Variety-specific redox regulation and metabolism proteins were also observed, suggesting functional diversity. Integrating solubility optimization with protein and metabolite characterization provides a comprehensive understanding of RBP composition, indicating its potential value as a plant protein source and functional food ingredient. This study highlights solubility optimization, protein and metabolite characterization, and the nutritional potential of RBP as a sustainable plant source for food applications.